Metastasis of ovarian cancer to the bile duct: a case report - Masahiro Shijo; Koji Fukase; Hideo Ohtsuka; Kyohei Ariake; Kunihiro Masuda; Masaharu Ishida; Masamichi Mizuma; Kei Nakagawa; Hiroki Hayashi; Takanori Morikawa; Fuyuhiko Motoi; Takeshi Naitoh; et al. (Surgical Case Reports)
Abstract Background Ovarian cancer typically spreads along the peritoneum or metastasizes through the blood or lymphatic stream. The bile duct is an extremely rare site of ovarian cancer-associated metastases. Case presentation A 55-year-old female underwent surgery for advanced left ovarian cancer 2 years ago. She was diagnosed with ovarian serous adenocarcinoma with multiple peritoneal metastases. She received chemotherapy for the residual peritoneal metastases. She achieved a clinical complete response and was followed up with imaging examinations for 1 year. She then complained of dark urine, yellowish discoloration of the eyes, and weight loss. Computed tomography showed an approximately 10-mm solid tumor at the hepatic hilum. Simultaneously, multiple peritoneal metastases were detected in the abdominal and pelvic cavity. Intraductal ultrasonography suggested that the hepatic hilum tumor was located in the bile duct wall. Tumor biopsy and brush cytology of the bile duct indicated atypical cells suspicious for carcinoma. After percutaneous transhepatic portal embolization, she underwent right hepatectomy and extrahepatic bile duct resection for the hepato-hilar tumor. The histopathological features were dysplastic cells with hyperchromatic nuclei and no dysplastic cells in the native biliary epithelium. Immunohistochemical staining revealed that the tumor cells were positive for CK-7 and WT-1 and negative for CK-20 and ER. These results suggested that the tumor was a metastasis of the ovarian serous adenocarcinoma. Conclusion This may be the first case of ovarian cancer metastasis to the bile duct. While it is extremely rare, ovarian cancer may metastasize to the hepatic duct, mimicking hilar cholangiocarcinoma.